4. The Value of Erythrocytes, Hemoglobin, and Hematocrit of Mice (Mus musculus) Exposed to Cigarette Smoke and Given Red Watermelon Extract (Citrullus vulgaris) - Yola Heryanita; Rusli Rusli; Rosmaidar Rosmaidar; Zuraidawati Zuraidawati; Rinidar Rinidar; Nuzul Asmilia; Muhammad Jalaluddin (Universitas Syiah Kuala, 2018)
The aim of this research was to investigate the effect of red watermelon (Citrullus vulgaris) extract to the value of erythrocytes, hemoglobin, and hematocrit of mice (Mus muscullus) exposed to cigarette smoke. This study followed direct complete randomized design by using 12 males’ mice which divided into 4 groups. The treatment group is divided by the negative control group which given 0,5 ml of aquadest, the positive control group which exposed to cigarette smoke and 0,5 ml of aquadest. The treatment group I was exposed to cigarette smoke and given red watermelon extract dose 22 mg/Bw mice. The treatment group II was exposed to cigarette smoke and given red with watermelon extract dose 44 mg/Bw mice. The exposure to cigarette smoke and the given of red watermelon extract were conducted for 30 days. The blood taking was performed on day 31 in the Plexus retroorbital. Furthermore, the number of erythrocytes, hemoglobin and hematocrit were calculated. The data were analyzed using ANOVA completely randomized design with SPSS for Windows 16.0. The results of this study showed that the extract of red watermelon for 30 days showed a highly significant effect (P 0.01) to the number of erythrocytes, hemoglobin, and hematocrit of mice. It is concluded that free radicals contained in the cigarette can cause a hemoglobin desaturation, increased blood viscosity, oxidative stress and red watermelon extract can minimize the damage.